Acer palmatum 'Bloodgood' - Edward F. Gilman (EDIS, 2004)
'Bloodgood' Japanese maple has a round shape with a height and spread of about 20 feet, making it nicely suited to residential landscapes (Figure 1). Its popularity is due mostly to the leaves, which stay red for most of the summer. Leaves turn greenish red during hot weather in the southern part of its range. The multiple trunks are muscular-looking, picturesque, grey and show nicely when lighted at night. Fall color is reddish and less striking than other Japanese maples. The globose canopy shape looks best when it is allowed to branch to the ground. Lower foliage branches can be thinned to display the attractive bark and trunk structure. This document is Fact Sheet FPS-009, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and and Agricultural Sciences, University of Florida. Publication date: October 1999.